Performance of potato (Solanum tuberosum L.) varieties with and without straw-mulch at Shankharapur, Kathmandu, Nepal - Shrestha, Kalyani; Sah, Shrawan Kumar; Singh, Reeti; Devkota, Yam Narayan (Journal of Agriculture and Natural Resources, 2020)
The suitability of crop varieties in a particular location determines the productivity of crops. A field experiment was conducted from February to May 2020 at Shankharapur, Kathmandu, Nepal to evaluate the growth and productivity of potato varieties with and without mulch. Five potato varieties (Cardinal, Janakdev, Khumal Bikas, MS- 42.3, Panauti Local) were evaluated under straw-mulch and no-mulch conditions. The treatments were arranged in two factorial Randomized Complete Block Design (RCBD) with 3 replications. The results revealed that the highest tuber yield was produced by Janakdev (34.29 t ha-1) followed by Panauti Local (29.52 t ha-1). Similarly, straw-mulch gave higher yield (25.9 t ha-1) as compared with no mulch condition (21.73 t ha-1). The higher tuber yield in the Janakdev and Panauti Local was because of higher tuber weight per hill, higher number and weight of medium size (50 -100 g) and oversize (> 100 g) tuber per hill. Similarly, higher yield in straw mulch was due to higher number and weight of tuber per hill. Higher gross return, net return was observed and the benefit cost ratioin varieties Janakdev (4.08) and Panauti Local (3.53) and rice straw mulch (2.88). Therefore, potato varieties Janakdev and Panauti Local with straw mulch are most suitable for Kathmandu like climate for improving productivity and profitability.